2023
DOI: 10.1002/lol2.10344
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Landsat surface reflectance archive for aquatic science: Implications for cloud‐based analysis

Daniel Andrade Maciel,
Nima Pahlevan,
Claudio Clemente Faria Barbosa
et al.

Abstract: Originally developed for terrestrial science and applications, the US Geological Survey Landsat surface reflectance (SR) archive spanning ~ 40 yr of observations has been increasingly utilized in large‐scale water‐quality studies. These products, however, have not been rigorously validated using in situ measured reflectance. This letter quantifies and demonstrates the quality of the SR products by harnessing a sizeable global dataset (N = 1100). We found that the Landsat 8/9 SR in the green and red bands margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Given the differences between the spectral response of Landsat sensors, we used this comprehensive set of surface reflectance observations to standardize surface reflectance across sensors. Recent studies have found that these differences, if not corrected for, can distort time‐series analyses and produce misleading downward trends (Maciel et al., 2023). This apparent bias has the potential to have widespread effects on the results of trend analyses of water quality data, where observed improvements in water quality trends (downward trends) is a product of these sensor differences.…”
Section: Methodsmentioning
confidence: 99%
“…Given the differences between the spectral response of Landsat sensors, we used this comprehensive set of surface reflectance observations to standardize surface reflectance across sensors. Recent studies have found that these differences, if not corrected for, can distort time‐series analyses and produce misleading downward trends (Maciel et al., 2023). This apparent bias has the potential to have widespread effects on the results of trend analyses of water quality data, where observed improvements in water quality trends (downward trends) is a product of these sensor differences.…”
Section: Methodsmentioning
confidence: 99%